ECG core curriculum - Zimmerman, Franklin H. (New York : McGraw Hill LLC, 2023)
"A conversational, reader-friendly, clinical approach to electrocardiography. A how-to-read ECG teaching tool that provides lessons from basic to advanced."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electrocardiography; Heart Diseases -- Diagnosis